Hubungan Faktor Individu dengan Lingkungan Terhadap Riwayat Penggunaan Napza Pada Remaja - Gusdiansyah, Edo; Sarli, Desi (Universitas Fort De Kock Bukittinggi, 2022)
Background: Drug abuse is a health problem that is of concern to the government as stated in the SDGs. The factors that cause drug users are social environmental factors such as curiosity motives, busy parents and lack of affection, broken home, personality factors such as low self-esteem, feelings of inferiority in society and the environment, the third emotional and mental such as a person's mental weakness will be more easy to influence the direction of use. The effects of drugs are dependence that has an impact on health, social, legal, economic and security. Efforts made to overcome these problems are usually counseling therapy, supportive psychotherapy. The purpose of the study was to determine the relationship between individual and environmental factors on the history of drug use. Methods: The type of research used is descriptive analytic with a cross sectional study approach. Result: The results obtained (53.8%) history of maladaptive drug use, (56.4%) with negative environmental factors, (56.4%) with negative individuals. There is a relationship between social environmental factors (p = 0.018), individual factors (p = 0.018) with a history of drug use. Conclusion: It is hoped that parents will be able to pay more attention, motivate, support and provide environmental facilities so that teenagers do not fall into the history of drug use.Keywords: History of Drug Use, Individuals, Environmental Factors